"Parasitically Occupying Bodies": Exploring Toxifying Securitization in Anti-Trans and Genocidal Ideologies. (2nd October 2022) - Owen, Leah
Abstract : What is the "internal logic" of extreme anti-minority ideologies? While phenomena such as dehumanization are widely recognized as playing an important role in legitimating mass violence, recent scholarship invites us to consider the impact of "toxification" and other securitizing and threat-framing discourses in motivating "defensive" action against minority groups. Using such a framework, this essay investigates anti-trans discourses that advocate for action against a supposed "trans epidemic". It finds that notions of infiltration, corruption, and intimate danger – associated with "toxifying" genocidal discourse – are likewise core to anti-trans ideological formations, with many distinctive elements in common. Where the two differ, however, is in their links with material security politics – genocidal toxification readily aligns with more "traditional" national security politics, something that has not occurred with anti-trans discourse. The essay concludes by identifying the practical and theoretical lessons that trans and genocide studies have for each other, as well as a future research agenda.